2002
DOI: 10.1210/endo.143.6.8839
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Luteinizing Hormone and Follicle-Stimulating Hormone in Male Siberian Hamsters by Exposure to Females and Photoperiod

Abstract: Siberian hamsters have decreased gonadotropin levels and testis size after short-day (SD) exposure. Upon transfer from short to long days, FSH and testis weight increase rapidly, whereas LH and T remain low for much longer. We investigated whether an additional environmental stimulus, specifically a female, could trigger an earlier release of LH and whether the response to the female was dependent on photoperiod. An increase in serum LH was induced in long day (LD), but not SD, males within minutes of female e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…Responses within these systems to female chemosignals are gated seasonally, and responsiveness is not rescued by T replacement in SD animals. These results mirror photoperiodic regulation of behavioral and neuroendocrine responses to female chemosignals (Morin and Zucker 1978;Miernicki et al 1990;Anand et al 2002). Thus, changes within the POA and RFRP neuronal system present a likely means by which photoperiod regulates processing of chemosensory cues to restrict reproduction to the appropriate season.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Responses within these systems to female chemosignals are gated seasonally, and responsiveness is not rescued by T replacement in SD animals. These results mirror photoperiodic regulation of behavioral and neuroendocrine responses to female chemosignals (Morin and Zucker 1978;Miernicki et al 1990;Anand et al 2002). Thus, changes within the POA and RFRP neuronal system present a likely means by which photoperiod regulates processing of chemosensory cues to restrict reproduction to the appropriate season.…”
Section: Discussionmentioning
confidence: 61%
“…As mentioned previously, exposure to female chemosignals elicits a rapid increase in LH and T in LD hamsters, presumably to facilitate reproductive behavior and function upon encountering a potential mate (Anand et al 2002;Richardson et al 2004;Nyby 2008). Investigation of the kisspeptin and RFRP systems, both potent upstream regulators of GnRH and LH release in male Syrian hamsters, revealed RFRP to be differentially responsive to female chemosignals across photoperiods.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In natural ecosystems, populations of wild rodents and some domesticated animals rely on photoperiod as a major proximate cue to control reproduction (Muteka et al 2006;Bronson 2009). However, some studies have shown that photoresponsive animals do not rely on photoperiod alone, but also on other changes in environmental conditions (Nelson et al 1983;Sicard et al 1993;Prendergast et al 2001;Anand et al 2002;Mutze 2007;Meheretu et al 2015;Fabio-Braga and Klein 2018). These may include ultimate factors such as food availability and social factors (Anand et al 2002;Meheretu et al 2015).…”
Section: Introductionmentioning
confidence: 99%